2009
DOI: 10.1002/bjs.6648
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of oesophageal anastomotic leaks by temporary stenting with self-expanding plastic stents

Abstract: In combination with effective drainage, self-expanding plastic stents are an option for the treatment of oesophageal anastomotic leaks, and may reduce leak-related morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 37 publications
2
73
1
10
Order By: Relevance
“…In more complex or extensive leakage a delayed reconstruction after diversion with a cervical esophagostomy may be required. However, surgical reintervention is associated with high morbidity and mortality (16)(17)(18) and prolonged intensive care unit and hospital stays, particularly in patients with a delayed diagnosis and mediastinal and pleural contamination. Endoscopy can define whether intrathoracic leakage is secondary to gastric conduit necrosis, conduit staple line dehiscence, or esophagogastric anastomosis dehiscence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more complex or extensive leakage a delayed reconstruction after diversion with a cervical esophagostomy may be required. However, surgical reintervention is associated with high morbidity and mortality (16)(17)(18) and prolonged intensive care unit and hospital stays, particularly in patients with a delayed diagnosis and mediastinal and pleural contamination. Endoscopy can define whether intrathoracic leakage is secondary to gastric conduit necrosis, conduit staple line dehiscence, or esophagogastric anastomosis dehiscence.…”
Section: Discussionmentioning
confidence: 99%
“…All leaks with less than 20 mm were solved endoscopically. Technical and clinical success was higher when time between surgery and SEMS placement was lower, even though without statistical significance (respectively, 10 days [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] vs. 48 days , p = 0.228 and 12 days [8][9][10][11][12][13][14][15][16][17][18][19][20][21] vs. 20 days , p = 0.374) (Fig. 1).…”
Section: Sems Placement and Adverse Eventsmentioning
confidence: 99%
“…Some studies [24][25][26] concluded that stent placement has been shown to be an excellent treatment in patients with mediastinal abscess in GEAL, while others [27] revealed that certain problems might be associated with stent placement and removal: insufficient closure of the leaks, stent migration and development of strictures after stent removal, severe complications such as bleeding and food blockage, and hard removal because of the growth of granulation tissue. Han et al [7] treated the patients of mediastinal abscess with stent placement and nasaloesophagus drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Auch hier sind die fehlende Standardisierung und der Mangel an prospektiven Studien wesentliche Faktoren, die die Einschätzung der Verfahren so schwierig machen [35]. Polyflex-Kunststoffstents [4,38,39] zeigen bei kleinen Fallserien von 5-22 Patienten eine Initialverschlussrate von 40-95% sowie einen definitiven Therapieerfolg bei 80-100%. Die Hauptkomplikation ist die Migration der Stents, die in bis zu 23% der Fälle auftritt.…”
Section: Therapie Bei Anastomoseninsuffizienzen Nach öSophagus- Und Munclassified